Experimental validation of an anti-windup design trading off position and heading direction control performance for quadrotor UAVs. Issue 22 (2022) - Marzagalli, Francesco; Ghignoni, Pietro; Gozzini, Giovanni; Invernizzi, Davide
Abstract: We present the experimental validation of a recently developed anti-windup design to guarantee stability and a desired level of performance in the presence of propellers saturation in quadrotor UAVs. The considered solution exploits a decentralized LMI-based compensator to mitigate directionality issues affecting saturated multi-variable plants and to achieve satisfactory time-domain performance for reference signals of interest. After discussing saturation effects in quadrotors, we first show how the compensator can be implemented on top of a popular cascade control architecture for underactuated multi-rotors and then how it can be tuned to prioritize position/heading direction control objectives. The design is finally validated through experiments in representative flight conditions.